Implementation of large, multi-site hospital interventions: a realist evaluation of strategies for developing capability - Janet C Long; Natalie Roberts; Emilie Francis-Auton; Mitchell N Sarkies; Hoa Mi Nguyen; Johanna I Westbrook; Jean-Frederic Levesque; Diane E Watson; Rebecca Hardwick; Kate Churruca; Peter Hibbert; Jeffrey Braithwaite (BMC, 2024)
Abstract Background This study presents guidelines for implementation distilled from the findings of a realist evaluation. The setting was local health districts in New South Wales, Australia that implemented three clinical improvement initiatives as part of a state-wide program. We focussed on implementation strategies designed to develop health professionals' capability to deliver value-based care initiatives for multisite programs. Capability, which increases implementers' ability to cope with unexpected scenarios is key to managing change. Methods We used a mixed methods realist evaluation which tested and refined program theories elucidating the complex dynamic between context (C), mechanism (M) and outcome (O) to determine what works, for whom, under what circumstances. Data was drawn from program documents, a realist synthesis, informal discussions with implementation designers, and interviews with 10 key informants (out of 37 identified) from seven sites. Data analysis employed a retroductive approach to interrogate the causal factors identified as contributors to outcomes. Results CMO statements were refined for four initial program theories: Making it Relevant- where participation in activities was increased when targeted to the needs of the staff; Investment in Quality Improvement- where engagement in capability development was enhanced when it was valued by all levels of the organisation; Turnover and Capability Loss- where the effects of staff turnover were mitigated; and Community-Wide Priority- where there was a strategy of spanning sites. From these data five guiding principles for implementers were distilled: (1) Involve all levels of the health system to effectively implement large-scale capability development, (2) Design capability development activities in a way that supports a learning culture, (3) Plan capability development activities with staff turnover in mind, (4) Increased capability should be distributed across teams to avoid bottlenecks in workflows and the risk of losing key staff, (5) Foster cross-site collaboration to focus effort, reduce variation in practice and promote greater cohesion in patient care. Conclusions A key implementation strategy for interventions to standardise high quality practice is development of clinical capability. We illustrate how leadership support, attention to staff turnover patterns, and making activities relevant to current issues, can lead to an emergent learning culture.